PENGARUH PEMAHAMAN PAJAK DAN E-SYSTEM PAJAK TERHADAP KEPATUHAN WAJIB PAJAK SERTA PERAN MODERASI KUALITAS PELAYANAN - Evieryata; Trisnawati, Estralita (Jurnal Kontemporer Akuntansi, 2025)
The Purpose of this study was to determine the effect of understanding tax regulations, implementing tax e-systems, and service quality on taxpayer compliance. Apart from that, this study also uses service quality to moderate the relationship between understanding tax regulations and taxpayer compliance and the relationship between implementing a tax e-system and taxpayer compliance. The data in this study uses primary data originating from a questionnaire survey using Google Form which was given to non-employee individual taxpayer respondents in Jakarta. Using the purposive sampling method, questionnaires from 120 respondents were completed and collected. From the results of the collected questionnaires, the researchers processed them using the smartPLS 4.0 program. The results of this study show that understanding tax regulations, implementing the tax e-system, and service quality have a positive and significant effect on non-employee individual taxpayer compliance. Meanwhile, service quality which plays a moderating role weakens the influence of understanding tax regulations and implementing the tax e-system on non-employee individual taxpayer compliance.